Study of vertical mass isolation structures equipped with metallic dampers with a focus on the position of stiff subsystem. (October 2021) - Farajiani, Farhad; Nekooei, Masoud; Mansoori, Mohammad Reza
Abstract: Vertical mass isolation approach is a new technique in which an individual structure is divided into two distinct subsystems and each possesses different characteristics. Such two subsystems–mass and stiff subsystems– are interconnected with passive dampers in vertical layers at the height of the frame. The primary task of such passive devices is to reduce the structure's seismic reactions by dissipating more of the seismic forces, as well as regulating the amount of structure displacement. In this paper, two models of stiff subsystem placement are introduced, the inner stiff subsystem(ISS) and the outer stiff subsystem(OSS). Structural models are introduced in two types of five and ten-story for both ISS and OSS systems. Metallic dampers were used as fuses to reconnect the isolated structures. For all models under seven distinct earthquake ground motions, nonlinear time history analyses were executed. The findings related to base shear forces, the shape of plastic hinges in structural components, the responses of roof acceleration, and the dampers' hysteresis behavior are studied. Based on the numerical data, the ISS system has a minor advantage over the OSS system in improving the structure's seismic efficiency and reducing seismic reactions.